Design and Implementation of the Marsh Climate Monitoring System Using the Internet of Things - Jbarah, Falah; Al-Mashhadi, Haider; Tahan, Marjan (Iraqi Journal for Electrical and Electronic Engineering, 2025)
The Internet of Things (IoT) has become a major enabler for sustainable development and has begun to have an impact on society as a whole. Marshes are significant ecosystems for the environment that are essential to biodiversity support and ecological equilibrium. However, environmental changes and human activity are posing an increasing threat to these fragile ecosystems. An Internet of Things (IoT)-based marsh monitoring system was created and put into operation to gather data in real-time on a variety of environmental factors, such as wind speed, CO2 and hydrogen levels, temperature, humidity, voltage, and current. The system makes use of a network of sensors spread out throughout the marsh, which may promote sustainable development. send data to a central node for processing before sending it to a platform hosted in the cloud. After that, an interactive online application is used to visualize the data, giving stakeholders important information about the condition and health of the marsh. Because the suggested system makes it possible to monitor and manage marsh ecosystems effectively, it may promote sustainable development.